2014
DOI: 10.1061/(asce)gt.1943-5606.0001014
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge Modeling Studies of Site Response in Soft Clay over Wide Strain Range

Abstract: Centrifuge modeling studies of site response in soft clay over wide strain range Abstract: Centrifuge models of soft clay deposits were shaken with suites of earthquake ground motions to study site response over a wide strain range. The models were constructed in an innovative hinged-plate container to effectively reproduce one dimensional ground response boundary conditions. Dense sensor arrays facilitate back-calculation of modulus reduction and damping values that show modest misfits from empirical models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…Recent work from Afacan et al [1] on centrifuge modeling of site response in soft clays over a wide range of strains that included nearly linear to strongly nonlinear soil behavior concluded that centrifuge tests using a hinged-plate container are valuable to understand 1-D seismic ground response and to validate nonlinear site response from empirical and numerical models. They did not present a comparison with numerical simulations in the paper, but according to the results presented, the Darendeli [5] functional form appeared to provide a reasonable characterization of the observed modulus-reduction behavior in the centrifuge models.…”
Section: Introductionmentioning
confidence: 98%
“…Recent work from Afacan et al [1] on centrifuge modeling of site response in soft clays over a wide range of strains that included nearly linear to strongly nonlinear soil behavior concluded that centrifuge tests using a hinged-plate container are valuable to understand 1-D seismic ground response and to validate nonlinear site response from empirical and numerical models. They did not present a comparison with numerical simulations in the paper, but according to the results presented, the Darendeli [5] functional form appeared to provide a reasonable characterization of the observed modulus-reduction behavior in the centrifuge models.…”
Section: Introductionmentioning
confidence: 98%
“…In this case, the surrounding soil may undergo large shear strains during earthquake shaking beyond the linear range which makes the accuracy of linear or equivalent linear models at least questionable. In support to the above, recent findings from centrifuge tests on the seismic behavior of soft clays under large intensity levels of input motions ( [15], [16], [17]) revealed attenuation of base acceleration as it propagates through the soil due to the inability of the soft clay to transmit shear stresses close to its limited shear strength. Stiffness degradation with the number of loading cycles has also been observed having a direct impact on the free-field loading imposed on piles [17].…”
Section: Introductionmentioning
confidence: 60%
“…Small misfits in the modulus reduction curve can translate to significant misfits in the stressstrain curve at high strain, resulting in errors in the desired shear strength (e.g. [4], [5], [6], [13]).…”
Section: Modulus Reduction Behavior Of Existing Modelsmentioning
confidence: 99%
“…This extrapolation can cause an under-or over-prediction of shear strength depending on the ratio of shear strength to small strain shear modulus, Gmax. These shear strength errors can translate to ground motion prediction errors [4,5,6]. Developing models that accurately capture small strain behavior and shear strength is obviously important for nonlinear site response simulations.…”
Section: Introductionmentioning
confidence: 99%